Study of Total Electron Content and Electron Density Profile from Satellite Observations During Geomagnetic Storms - Rana, B. B.; Chapagain, N. P.; Adhikari, B.; Pandit, D.; Pudasainee, K.; Chapagain, S.; Chhatkuli, D. (Journal of Nepal Physical Society, 2019)
Total Electron Content (TEC) and electron density profile are the key parameters in the mitigation of ionospheric effects on radio wave communication system. In this study, the variations of TEC and electron density profile have been analyzed using satellite data from four different latitude-longitude sectors (13°N -17°N, 88°E - 98°E), (30°N - 50°N, 95°W - 120°W), (26°S - 29°S, 163°W - 167°W,) and (45°S - 60°S, 105°W-120°W) during different geomagnetic storms. The interplanetary magnetic field (Bz), solar wind velocity (Vsw), solar wind pressure (Psw) and geomagnetic indices, aurora index -AE, Kp and disturbed stormed time index (Dst) are also analyzed to distinguish their effects on TEC and electron density. The geomagnetic indices and solar wind parameters are correlated with the TEC and electron density. The study showed that the value of TEC and electron density vary significantly with different latitude, longitude, altitude and solar activities. The result also concludes that the electron density profile increases with the altitude, acquired peak value around 250km-300km and decreased beyond the altitude of 300 km.